(untitled) - Owen, Claudia (Belmont, CA, 2006)
Utilizing graphs and simple calculations, this clearly written lab manual complements the study of earth science or physical geology. Engaging activities are designed to help you develop data-gathering skills (e.g., mineral and rock identification) and data-analysis skills. You'll learn how to understand aerial and satellite images; to perceive the importance of stratigraphic columns, geologic sections, and seismic waves; and more
Keywords: Earth sciences,Khoa học trái đất; Sách giáo khoa